Characterisation of dislocation behaviour in RPV steel - Monnet, G.; Domain, C.; Bacon, D.; Terentyev, D. (Вопросы атомной науки и техники, 2009)
Results obtained in the framework of the European project PERFECT (FI60-CT-2003-
208840) are presented. Наводяться результати, отримані у рамках Європейського проекту PERFECT (F160-CT-
2003-208840). Приводятся результаты, полученные в рамках Европейского проекта PERFECT (F160-
CT-2003-208840).